Fluorouracil and bevacizumab plus anakinra for patients with metastatic colorectal cancer refractory to standard therapies (IRAFU): a single-arm phase 2 study. (2nd September 2018) - Isambert, Nicolas; Hervieu, Alice; Rébé, Cedric; Hennequin, Audrey; Borg, Christophe; Zanetta, Sylvie; Chevriaux, Angélique; Richard, Corentin; Derangère, Valentin; Limagne, Emeric; Blanc, Julie; Bertaut, Aurélie; et al.
ABSTRACT: In preclinical models, IL-1β inhibition could enhance the efficacy of fluorouracil (5-FU). In this phase 2 study, we assessed the activity and safety of 5-FU plus bevacizumab and anakinra (an IL-1β and α inhibitor) in patients with metastatic colorectal (mCRC) refractory to chemotherapy and anti-angiogenic therapy. Eligible patients had unresectable mCRC; were refractory or intolerant to fluoropyrimidine, irinotecan, oxaliplatin, anti-VEGF therapy, and anti-EGFR therapy (for tumors with wild-type KRAS ). Patients were treated with a simplified acid folinic plus 5-FU regimen and bevacizumab (5 mg/kg) both administered by intravenous infusion for 30 min every 2 weeks. Anakinra (100 mg) was injected subcutaneously once daily. The primary endpoint was the 2-month response rate determined upon CHOI criteria. Thirty two patients with metastatic colorectal cancer were enrolled. Five patients demonstrated response (Choi criteria) and 22 patients had stable disease as the best 2-month overall response. Median progression-free and overall survival were 5.4 (95% CI, 3.6–6.6) and 14.5 months (95% CI, 9–20.6) respectively. Twenty patients experienced grade 3 toxicity. No grade 4 or 5 toxicity related to therapy occurred. The most common grade 3 adverse events were neutropenia in 8 (25%) patients, digestive side effects in 7 (21.9%) patients and hypertension in 6 (18.75%) patients. No treatment-related deaths or serious adverse events were reported.5-FU plus bevacizumab and anakinra has promising activity and a manageable safety profile, suggesting that this combination might become a potential treatment option for patients with refractory mCRC.